Direct Determination of the Site of Addition of Glucosyl Units to Maltooligosaccharide Acceptors Catalyzed by Maize Starch Synthase I - Xie, Ying; Barb, Adam W.; Hennen-Bierwagen, Tracie A.; Myers, Alan M. (Frontiers in Plant Science, 2018)
Starch synthase (SS) (ADP-glucose:1,4-α-D-glucan 4-α-D-glucosyltransferase) elongates α (1→4) linked linear glucans within plastids to generate the storage polymers that constitute starch granules. Multiple SS classes are conserved throughout the plant kingdom, indicating that each provides a unique function responsible for evolutionary selection. Evidence has been presented arguing for addition of glucosyl units from the ADPglucose donor to either the reducing end or the non-reducing end of the acceptor substrate, although until recently direct evidence addressing this question was not available. Characterization of newly incorporated glucosyl units determined that recombinant maize (Zea mays L.) SSIIa elongates its substrates at the non-reducing end. However, the possibility remained that other SSs might utilize distinct mechanisms, and that one or more of the conserved enzyme classes could elongate acceptors at the reducing end. This study characterized the reaction mechanism of recombinant maize SSI regarding its addition site. Newly incorporated residues were labeled with 13C, and reducing ends of the elongation products were labeled by chemical derivitization. Electrospray ionization-tandem mass spectroscopy traced the two parameters, i.e., the newly added residue and the reducing end. The results determined that SSI elongates glucans at the non-reducing end. The study also confirmed previous findings showing recombinant SSI can generate glucans of at least 25 units, that it is active using acceptors as short as maltotriose, that recombinant forms of the enzyme absolutely require an acceptor for activity, and that it is not saturable with maltooligosaccharide acceptor substrates.